Uma metodologia para controle e compensação posicional automática de um arranjo submarino - Ferreira, Alex Bolhosa (2019)
This dissertation proposes a methodology for the positional control of an underwater array that can be used for any other submerged objects that one wishes to control. The study was performed with only one degree of freedom and could be extended to other grades with a consequent increase in complexity. The azimuth positional control was chosen so that the array could have a control of its direction in relation to the magnetic north, allowing a better transmission / reception power in the desired direction and presenting itself as a mechanical equivalent to the adaptive beamforming technique, with less computational effort. A prototype was constructed and after hundreds tests performed the preliminary theoretical analyzes was ratified.